2017
DOI: 10.3389/fpls.2017.01458
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Regulation of Soybean SUMOylation System under Abiotic Stress Conditions

Abstract: Covalent attachment of the small ubiquitin-related modifier, SUMO, to substrate proteins plays a significant role in plants under stress conditions, which can alter target proteins' function, location, and protein-protein interactions. Despite this importance, information about SUMOylation in the major legume crop, soybean, remains obscure. In this study, we performed a bioinformatics analysis of the entire soybean genome and identified 40 genes belonged to six families involved in a cascade of enzymatic react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…A variety of abiotic stresses are known to cause the accumulation of SUMO conjugates, including oxidative stress, salt, drought, and temperature stresses [1,20,23]. Despite the well characterization of the SUMOylationdependent abiotic stress responses in Arabidopsis, there is growing evidence that this link is conserved in many crop species such as rice, maize or soybean [41][42][43][44]. For example, the levels of SUMO conjugates increase in response to abiotic stress such as cold, high salinity or increased ABA in rice [44], and in response to heat and oxidative stress in maize [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of abiotic stresses are known to cause the accumulation of SUMO conjugates, including oxidative stress, salt, drought, and temperature stresses [1,20,23]. Despite the well characterization of the SUMOylationdependent abiotic stress responses in Arabidopsis, there is growing evidence that this link is conserved in many crop species such as rice, maize or soybean [41][42][43][44]. For example, the levels of SUMO conjugates increase in response to abiotic stress such as cold, high salinity or increased ABA in rice [44], and in response to heat and oxidative stress in maize [43].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the levels of SUMO conjugates increase in response to abiotic stress such as cold, high salinity or increased ABA in rice [44], and in response to heat and oxidative stress in maize [43]. Moreover, the levels of SUMO conjugates also increase in the soybean plants that are exposed to various abiotic stresses including high salinity, heat or increased ABA [41,42]. Our results showed that SUMO conjugates on protein level increased initially and then decreased, when seedlings subjected to salt stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that the characterization of SUMOylation-dependent abiotic stress responses has been studied mostly in Arabidopsis, there is growing evidence that this link is conserved in many crop species such as rice, maize or soybean. The expression of the SUMOylation machinery components in those species is also developmentally controlled (Augustine et al, 2016;Chaikam and Karlson, 2010;Li et al, 2017;Reed et al, 2010). Furthermore, conjugate levels increase in response to abiotic stress such as cold, high salinity or increased ABA in rice (Chaikam and Karlson, 2010), and in response to heat stress in poplar (Reed et al, 2010).…”
Section: Sumoylation and Abiotic Stress In Model Species And Cropsmentioning
confidence: 99%
“…With the increase in amount of SUMOylated proteins, the levels of the free SUMO levels decrease. Following this with the relief of stress amount of free SUMO levels increases rapidly [13]. Moreover, mutants missing the SIZ1 allele were susceptible to abiotic stresses.…”
Section: Introductionmentioning
confidence: 96%